AHR2 Mutant Reveals Functional Diversity of Aryl Hydrocarbon Receptors in Zebrafish - Goodale, Britton C.; La Du, Jane K.; Bisson, William H.; Janszen, Derek B.; Waters, Katrina M.; Tanguay, Robert L. (PloS one, 2012)
The aryl hydrocarbon receptor (AHR) is well known for mediating the toxic effects of TCDD and has been a subject of intense research for over 30 years. Current investigations continue to uncover its endogenous and regulatory roles in a wide variety of cellular and molecular signaling processes. A zebrafish line with a mutation in ahr2 (ahr2(hu3335)), encoding the AHR paralogue responsible for mediating TCDD toxicity in zebrafish, was developed via Targeting Induced Local Lesions IN Genomes (TILLING) and predicted to express a non-functional AHR2 protein. We characterized AHR activity in the mutant line using TCDD and leflunomide as toxicological probes to investigate function, ligand binding and CYP1A induction patterns of paralogues AHR2, AHR1A and AHR1B. By evaluating TCDD-induced developmental toxicity, mRNA expression changes and CYP1A protein in the AHR2 mutant line, we determined that ahr2(hu3335) zebrafish are functionally null. In silico modeling predicted differential binding of TCDD and leflunomide to the AHR paralogues. AHR1A is considered a non-functional pseudogene as it does not bind TCCD or mediate in vivo TCDD toxicity. Homology modeling, however, predicted a ligand binding conformation of AHR1A with leflunomide. AHR1A-dependent CYP1A immunohistochemical expression in the liver provided in vivo confirmation of the in silico docking studies. The ahr2(hu3335) functional knockout line expands the experimental power of zebrafish to unravel the role of the AHR during development, as well as highlights potential activity of the other AHR paralogues in ligand-specific toxicological responses.